2000
DOI: 10.1046/j.1365-2958.2000.02111.x
|View full text |Cite
|
Sign up to set email alerts
|

The Vibrio cholerae ToxR/TcpP/ToxT virulence cascade: distinct roles for two membrane‐localized transcriptional activators on a single promoter

Abstract: ToxR is required in Vibrio cholerae for transcriptional activation of the toxT gene, the protein product of which activates numerous genes involved in virulence. Although ToxR cannot activate the toxT promoter in Escherichia coli, the products of the tcpPH operon are shown here to activate the toxT promoter, and co‐expression with ToxRS enhances activation. An identical pattern was seen in a ΔtcpPΔtoxR strain of V. cholerae when TcpPH or ToxRS was expressed from plasmids. Although overexpression of the TcpP/H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
264
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(275 citation statements)
references
References 44 publications
10
264
1
Order By: Relevance
“…CRP bound to -310 et al, 1998;Li et al, 2000). Krukonis et al (2000) recently showed that, at the toxT promoter, ToxR acts as a coactivator of TcpP, demonstrating for the first time the possibility that ToxR-dependent transcription regulation involves other transcription factors in addition to RNAP. Our finding that ToxR represses ompT transcription through an antiactivation mechanism further illuminates the important aspect of ToxR as a global transcription regulator.…”
Section: Mechanism Of Crp-dependent Activation At the Ompt Promotermentioning
confidence: 99%
See 3 more Smart Citations
“…CRP bound to -310 et al, 1998;Li et al, 2000). Krukonis et al (2000) recently showed that, at the toxT promoter, ToxR acts as a coactivator of TcpP, demonstrating for the first time the possibility that ToxR-dependent transcription regulation involves other transcription factors in addition to RNAP. Our finding that ToxR represses ompT transcription through an antiactivation mechanism further illuminates the important aspect of ToxR as a global transcription regulator.…”
Section: Mechanism Of Crp-dependent Activation At the Ompt Promotermentioning
confidence: 99%
“…Using phage CP-T1ts-mediated generalized transduction (Hava and Camilli, 2001), crp was inactivated in a toxR mutant of 395, EK307 (Krukonis et al, 2000), generating the double mutant SCL100 (toxR -crp -). The growth phasedependent regulation of OmpT expression in wild-type 395 was then compared with that in EK307 (toxR -), KSK377 (crp -) and SCL100 (toxR -crp -).…”
Section: Crp Is Required For Ompt Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptional regulation of CT has been extensively studied. Expression of the ctx gene encoding CT is controlled by a regulatory cascade involving two cytoplasmic membrane pairs, ToxS/ToxR and TcpP/ TcpH, and an AraC-like activator, ToxT (DiRita et al, 1991;Higgins et al, 1992;Skorupski & Taylor, 1997;Hase & Mekalanos, 1998;Krukonis et al, 2000). In contrast, little is known about the regulation of the eltAB operon.…”
Section: Introductionmentioning
confidence: 99%